Sandwiched cathodes kinetically boosted by few‐layered catalytic 1T‐MoSe2 nanosheets for high‐rate and long‐cycling lithium‐sulfur batteries. Issue 5 (9th February 2023) - Xu, Jun; Tang, Heng; Cao, Shoufu; Chen, Xiaoyi; Chen, Zhao; Ma, Yuanming; Zhang, Yan; Chen, Junwei; Lu, Xiaoqing; Lee, Chun‐Sing
Abstract: An advanced electrocatalyst to accelerate the sluggish kinetics of multistep redox reactions and suppress the severe shuttle effects is desirable in Li‐S batteries (LSBs). Phase engineering can provide a fascinating way to modulate electronic structures and boost catalytic activity of electrocatalysts. In this study, few‐layered 1T‐MoSe2 nanosheets grown on carbon cloth (1T‐MoSe2 /CC) are synthesized and employed as a multifunctional interlayer as well as a catalytic 3D current collector in LSBs to promote both physiochemical confinement and catalytic conversion toward lithium polysulfides (LiPSs). Density functional theory (DFT) calculations reveal that 1T‐MoSe2 has metallic properties beneficial for rapid electronic transport and exhibits a superior catalytic activity to reduce the Gibbs free energy barriers toward LiPS conversion. Significant improvements in chemisorption toward LiPSs, diffusion coefficients of Li ions, and Li2 S deposition/decomposition reaction kinetics are realized by the 1T‐MoSe2 /CC film. Consequently, the Al@S/AB@1T‐MoSe2 /CC LSB, where 1T‐MoSe2 /CC is used an interlayer, presents high rate capability of 1253 (1C), 1052 (2C) and 882 (4C) mAh g −1 and excellent long‐term cycling stability at a high rate (2000 cycles at 4C) with a low capacity fading rate (0.017% per cycle). Moreover, with a sandwiched cathode of 1T‐MoSe2 /CC@S/AB@1T‐MoSe2 /CC, where 1T‐MoSe2 /CC works as both a catalytic 3D current collector and a multifunctional interlayer, the LSB at high S loading of 5.7 mg cm −2 and low electrolyte/sulfur ratio of 7.8 μL mg −1 exhibits a high initial areal capacity of 5.43 mAh cm −2 and remarkable rate‐cycling performance (200 cycles). Abstract : Metallic 1T‐MoSe2 grown on carbon cloth (1T‐MoSe2 /CC) is fabricated to work as catalytic current collector and multifunctional interlayer for high‐performance lithium‐sulfur batteries. Advanced sandwiched cathode is designed to promote the physical encapsulation, chemical entrapment and catalytic conversion of polysulfide species to suppress the shuttle effect.